Analysis of fish viral disease epidemic situation worldwide - D. K. Pavlov; A. A. Pichuyeva (Ветеринария сегодня)
The epidemic situation on aquaculture diseases worldwide is of relevance for our country as this information makes it possible to imagine a risk of infection spread among countries and to determine effectiveness of necessary measures aimed at prevention of these diseases spread in territories of neighboring and other countries. The epidemiological monitoring is the basis for rational planning and effective arrangement of measures for controlling fish infectious diseases.